Lion & Sons Company Furniture Store - Gordon, John C. (photographer):::Creator::::::::::::
Lion & Sons furniture store located at Second and San Fernando Streets in San Jose. Signs read: "L. Lion & Sons Co., Incorporated. Established 1856;" "Lion's;" "Carpets;" "Furniture;" "Draperies." A car is parked at the curb in front of the store. Pedestrians walk by.